Redefining Herd Health: No-Antibiotic Strategies for Revolutionizing Sustainable Dairy Development - Md. Emran Hossain (International Journal of Cell Biology and Cellular Functions, 2026)
This study investigates the potential of no-antibiotic strategies to transform herd health management andpromote sustainable dairy development. Rising concerns over antimicrobial resistance (AMR) and the environmental consequences of antibiotic use have intensified the demand for alternative, sustainable disease management approaches. No-antibiotic strategies emphasize preventive health measures, biosecurity, and holistic practices, including optimized nutrition, vaccination, and natural antimicrobial alternatives. The study evaluates diverse management interventions, such as precision livestock farming, genetic selection for disease resistance, and the use of probiotics, prebiotics, and essential oils, to strengthen herd immunity and reduce disease incidence. It also highlights the importance of improved housing systems, stress management, and pasture-based practices in maintaining animal health without antibiotics. Integrating these strategies provides dual benefits, enhancing animal welfare while supporting the long-term sustainability of dairy operations. By shifting from reactive to preventive health measures, no-antibiotic approaches not only improve productivity but also mitigate public health risks associated with AMR. This study offers a comprehensive review of current no-antibiotic strategies and presents practical recommendations for their implementation globally, aiming to establish dairy systems that are both economically viable and environmentally responsible.
Keywords: Antimicrobial resistance; biosecurity; herd health; natural antimicrobials; preventive management; sustainable dairy; vaccination strategies